Pharmacokinetic and Drug-Drug Interaction Profiles of the Combination of Tezacaftor/Ivacaftor - Varun Garg; Jinshan Shen; Chonghua Li; Sagar Agarwal; Asfiha Gebre; Sarah Robertson; Jiayin Huang; Linda Han; Licong Jiang; Kristin Stephan; Linda T. Wang; Julie Lekstrom‐Himes (Wiley, 2019)
Drug-drug interaction (DDI) studies are described for tezacaftor/ivacaftor, a new cystic fibrosis transmembrane conductance regulator modulator therapy for the treatment of cystic fibrosis. Three phase I DDI studies were conducted in healthy subjects to characterize the DDI profile of tezacaftor/ivacaftor with cytochrome P450 (CYP)3A substrates, CYP3A inhibitors, and a permeability glycoprotein (P‐gp) substrate. The effects of steady‐state tezacaftor/ivacaftor on the pharmacokinetics (PKs) of digoxin (a P‐gp substrate), midazolam, and ethinyl estradiol/norethindrone (CYP3A substrates) were evaluated. Effects of strong (itraconazole) and moderate (ciprofloxacin) CYP3A inhibitors on tezacaftor/ivacaftor PKs were also determined. Tezacaftor/ivacaftor increased digoxin area under the curve (AUC) by 30% but did not affect midazolam, ethinyl estradiol, or norethindrone exposures. Itraconazole increased the AUC of tezacaftor 4‐fold and ivacaftor 15.6‐fold. Ciprofloxacin had no significant effect on tezacaftor or ivacaftor exposure. Coadministration of tezacaftor/ivacaftor may increase exposure of sensitive P‐gp substrates. Tezacaftor/ivacaftor is unlikely to impact exposure of drugs metabolized by CYP3A, including hormonal contraceptives. Strong CYP3A inhibitors significantly increase the exposures of tezacaftor and ivacaftor.